Prospective Screening for Primary Aldosteronism in Patients With Suspected Obstructive Sleep Apnea. Issue 6 (26th April 2021) - Chee, Min Ru; Hoo, Jesse; Libianto, Renata; Gwini, Stella M.; Hamilton, Garun; Narayan, Om; Young, Morag J.; Fuller, Peter J.; Yang, Jun
Abstract : Supplemental Digital Content is available in the text. Abstract : Several studies have demonstrated a bidirectional relationship between obstructive sleep apnea and primary aldosteronism (PA); however, many of these studies are limited to patients with known obstructive sleep apnea, hypertension, or PA. We evaluated the role of screening for PA in all patients referred for a diagnostic sleep study without selecting for prior diagnoses with these conditions. Plasma aldosterone and renin concentration were measured after an overnight polysomnography. Blood pressure was measured at the sleep center for all patients, while a proportion underwent 24-hour blood pressure monitoring. Of the 85 participating patients, 2 (2.4%) were identified to have likely PA based on an elevated aldosterone:renin ratio and/or clinical characteristics. Another 10 (11.8%) were identified to have possible PA based on their low or normal plasma renin concentration despite taking antihypertensive medications that are known to elevate renin. In participants with both obstructive sleep apnea and hypertension (n=40), the prevalence of likely or possible PA was 30%. However, there was no correlation between aldosterone, rennin, or aldosterone:renin ratio and the apnea-hypopnea index using multiple regression analysis adjusted for interfering medications and hypertension status. The observed high prevalence of possible PA among those with both hypertension and obstructive sleep apnea suggests that they should be routinely screened for PA.